The Juvenile Advocate Society, 1821‑1826: Self-Proclaimed Schoolroom for Upper Canada’s Governing Class - Baker, G. (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1985)
AbstractThe emergence of professions in Upper Canada has yet to be the subject of detailed examination or in-depth comparative analysis. Work so far has tended to be biograph- ical, institutional or functional in orientation. Thus the emergence of a professional consciousness in the colony is even less well-researched than the whole context of professionalization.A preliminary reconstruction of the self-image of members of the Bar, and their perceptions of such concepts as privilege, destiny and responsibility, is attempted through an examination of the early records of the Juvenile Advocate Society. This organization of law students was active in York (Toronto) roughly between 1821 and 1826. Since legal culture - the rhetoric, concepts and self-perceptions of members of the professional community - both reflects and generates social order, the debates of this society offer a suggestive entrée to an emergent professional consciousness.The Juvenile Advocate Society offered a unique opportunity for senior members of the Bar to inculcate the values which underlay the colony's legal system to its members. Its participants included senior barristers of varied political persuasions, like William Warren Baldwin and Henry John Boulton. The organization was the first of several ambitious attempts to socialize law students, part of an attempt to replicate and expand their highly valued provincial aristocracy.As an informal schoolroom for the colony's self-proclaimed elite, the Juvenile Advocate Society aped the structures as well as the values of the provincial adminis- tration. Topics for discussion and the rules of procedure underlined the society's role in teaching law students "proper" values. These extended beyond the traditional realm of politics to include the relationship of culture to the constitution, of private and public spheres of activity, and secular social structures to sacredly ordained order. Whether this training was a passport to authority, status and gentility is uncertain, but the efforts to ensure the continuance of this group of ideas in new generations suggest that members of the elite thought it worth the attempt.